PENGARUH RADIASI DAN LOKASI TUMBUH TERHADAP PERTUMBUHAN DAN PENYAKIT HAWAR DAUN TALAS kv KETAN - L Agus Sukamto; Saefudin Saefudin (BERITA BIOLOGI, 2010)
Taro (Colocasia esculenta (L.) Schott) is an important tuber crop, grown widely in humid tropics and a source of carbohydrate for many people in Asia, Africa, and the Pacific islands. The leaves and stalks of taro are used as vegetable, as they contain a high protein that is useful for people diet in developing countries. Taro is underutilized plant that has potency as an alternative food.Plant propagation of taro is usually done by using its rhizome or stolon so that the genetic diversity is very limited. In vitro and irradiated techniques can increase its genetic diversity and multiply the plant that has superior quality and quantity.Taro "Ketan" grown tissue culture have been irradiated with gamma rays S Gy and 10 Gy were planted on two different environmental locations.There were many variants as the results of these treatments. Gamma rays and environmental locations caused genotype changes that were stolon number, plant height, corm fresh weight, and leaf blight disease.Gamma rays caused morphological changes that were orientation, undulation, outline of sinus, margin of lamina,and petiole color.